KETAHANAN LIMA JENIS KAYU ASAL CIANJUR TERHADAP JAMUR - Sihati Suprapti; Djarwanto (Jurnal Penelitian Hasil Hutan, 2013)
The resistance property against eleven strain of fungal attack of fire lesser-known wood species namely ki hiur (Castanopsis acurtunatissima ADC), baru pedes (Cinnamomun inets Reinw Ex Blume.), buru boys (Litsca angulata Bl), ki kanteb (Ficus nervosa Heyni), and ki bonem (Horsfieldia glabra Park), were evaluated using Kalle-flask method. Samples of every wood species were divided into two groups, namely onder and inner parts of log. The reults indicated that all of five wond species is categorized at not-resistant against fungal attack (class II. The avight lass of the inner part of 14.99% was lower than that of the outer part of logs (15.76%). Howvrer, both parts are classified as not-resistant wood (class IV) to the fungal attack. The highest weight loss wat occurred on the inner part log of Cinnamomun iners which was expated to Puпороги вапнінен ННBI-324 (56.19%). The fungal capability to decay wwed from the highest to the boavst arr Pycnoporus sanguincus HHBI-324, Tytomyces palustris, Trametes. Schizophyllum commune, Pubporus, Coriolus veracolor. Pustia plasenta. Lentuous lepideus. P. sanguineus HFIBI 8149, Dactyopinax spathularia, and Chactomium globosum.